Q: 6x plus 11 equals 3x plus 15?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

3x+4=-11 3x=-15 x=-5

x = -11

3x + 4 = -11 Subtract 4 from both sides: 3x = -15 Divide both sides by 3: x = -5

3x+12x = 15 15x = 15 x = 1

5x+3 = 3x+11 5x-3x = 11-3 2x = 8 x = 4

Related questions

3x+4=-11 3x=-15 x=-5

x = -11

no

3x + 4 = -11 Subtract 4 from both sides: 3x = -15 Divide both sides by 3: x = -5

3x+11+5x=75(add 5x and 3x) 8x+11=75(-11) 8x=64(/ 8) x=8(ANSWER)

3x+12x = 15 15x = 15 x = 1

-3x + 5 + 6 = -15 Multiply by -1 (swap all signs): 3x - 5 - 6 = 15 Combine like terms on left side: 3x - 11 = 15 Add 11 to both sides: 3x = 26 Divide both sides by 3: x = 26/3 or 8.66...

5x+3 = 3x+11 5x-3x = 11-3 2x = 8 x = 4

Where is y in the first equation, you put its equivalent (=) -3x + 11 The first equation is then transformed into: 3x + 2*(-3x + 11) = 7. Then you get: 3x + (-6x) + 2*11 = 7 <=> -3x + 22 = 7 <=> 22 - 7 = 3x <=> 3x = 15 <=> x = 15/3 <=> x = 5. Then you substitute the x in the second equation by its equivalent so, (x = 5) y = -3*x + 11 <=> y = -3*5 + 11 <=> y = -15 + 11 <=> y = -4. x = 5. y = -4.

(0,7)

15 + 14 + 14 + 11 + 2x + x = 75 Collect like terms 54 + 3x = 75 Subtract 54 3x = 21 Divide by 3 x = 7 ■

3x + 11 = x + 3 2x = -8 x = -4